STRUKTUR DAN INTEGRASI PASAR EKSPOR LADA HITAM DAN LADA PUTIH DI DAERAH PRODUKSI UTAMA - DJULIN, ADIMESRA; MALIAN, A. HUSNI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 1 Februari 2005)
Pepper agribusiness in Indonesia has contributed to farmer’s income generation and national foreign exchange earnings. Most pepper export destination is Singapore or United States of America. Annual growth rate of pepper export value during 1989-1998 was 9.0%, although there was a decrease in 2001. The objective of the study is to identify pepper market structure and integration in Indonesia. Selected study sites are main production centers which are Lampung Province for black pepper and Bangka-Belitung Propince for white pepper. Various primary and secondary data had been collected from various sources. An analysis model of market integration of modified Ravallion Model (1986) was applied. The result shows that black pepper farm gate price is not integrated with exporter’s gate price, while the exporter’s gate price and the world’s price is weakly integrated. In addition, white pepper farm gate price is integrated very weakly with exporter’s gate price; in contrast the exporter’s gate price is strongly integrated with the world’s pepper price. This strong integration reflects that domestic price movement is heavily affected by international price fluctuation. This indicates that pepper commodity development should take efficiency and world market competitiveness into consideration.
Keywords: Pepper, Market Integration, Efficiency and Competitiveness.